MSG: AN OVERVIEW ON THE ILL EFFECTS OF THE INGREDIENT IN HUMAN FOOD CHAIN - Ganguly, Subha (International Journal of Research -GRANTHAALAYAH, 2017)
Monosodium glutamate, also known as MSG and sodium glutamate is used as a flavor enhancer especially in Chinese restaurant foods and snacks. It was first prepared in 1908 by Japanese biochemist Kikunae Ikeda, who was trying to isolate and duplicate the savory taste of edible seaweed called kombu, which is used as a base for many Japanese soups.[1]